IXPE and Multiwavelength Observations of Blazar PG 1553+113 Reveal an Orphan Optical Polarization Swing - Middei R.; Perri M.; Puccetti S.; Liodakis I.; Di Gesu L.; Marscher A.P.; Cavero N.R.; Tavecchio F.; Donnarumma I.; Laurenti M.; Jorstad S.G.; Agudo I.; et al. (IOP Publishing Ltd, 2025)
The lower-energy peak of the spectral energy distribution of blazars has commonly been ascribed to synchrotron radiation from relativistic particles in the jets. Despite the consensus regarding jet emission processes, the particle acceleration mechanism is still debated. Here, we present the first X-ray polarization observations of PG 1553+113, a high-synchrotron-peak blazar observed by the Imaging X-ray Polarimetry Explorer (IXPE). We detect an X-ray polarization degree of (10 ± 2)% along an electric-vector position angle of ψX = 86° ± 8°. At the same time, the radio and optical polarization degrees are lower by a factor of ∼3. During our IXPE pointing, we observed the first orphan optical polarization swing of the IXPE era, as the optical angle of PG 1553+113 underwent a smooth monotonic rotation by about 125°, with a rate of ∼17° day–1. We do not find evidence of a similar rotation in either radio or X-rays, which suggests that the X-ray and optically emitting regions are separate or, at most, partially cospatial. Our spectropolarimetric results provide further evidence that the steady-state X-ray emission in blazars originates in a shock-accelerated and energy-stratified electron population.